Cytological diagnosis of microfilaria coexistent with suspected malignancy of breast and ovary in a young pregnant female. (July 2022) - Singh, Sunita; Gill, Meenu; Dalal, Niti; Gupta, Veena; Jain, Promil; Gupta, Sumiti
Filariasis is a major health issue of tropical and subtropical regions and is endemic in India. It is rarely seen in cytological smears, exfoliative scrapings or in effusions. We present the case of a 29-year old female with filaria found on cytological examination of both breast and ovary.